The Effect of Health Education on Student Knowledge in First Aid Emergency Response to Accidents at SMPN 3 Limboto - Indriyani Panigoro (Universitas Muhammadiyah Palu, 2026)
Emergencies often cause panic especially in teenagers or students and one of the factors is the lack of knowledge, so it is important to increase knowledge about the procedures to provide assistance in medical emergency situations by providing education. This study aims to determine the influence of health education on first aid knowledge in accidents. The research design uses quantitative with quasi-experimental methods, one-group pretest-posttest, the number of population, namely all grade IX students as many as 67 students while the number of samples is 67 students or total sampling, this study uses the Wilcoxon test. The results of the study were the knowledge of students before being given the highest educational intervention, namely the adequate category of 58 people and the lowest category of good as many as 9 people, while the knowledge of students after being given first aid education in the highest accident was the good category of 66 people and the lowest category was the sufficient category of 1 person, the results of the Wilcoxon test obtained a significant value0.000. Conclusion There is an effect of health education on the knowledge of female students in emergency response to first aid in accidents at SMPN 3 Limboto. Suggestions for schools to collaborate with health workers to provide education or training to students about emergency response to first aid in accidents.